Epidemiological Study of Fatal Head Injury in Road Traffic Accident Cases: A Study from BPKIHS, Dharan (Health Renaissance, 2011)
Setting: Study was performed in mortuary of B P Koirala Institute of Health Sciences (BPKIHS), Dharan. Objectives: 1. To know the various epidemiological factors related to road traffic accident cases. 2. To know the relationship of head injury in road traffic accidents with the factors like helmet use, type of vehicle involved in accident. Study design: longitudinal descriptive study. Study unit: 77 Dead bodies with fatal head injury from RTA coming to BPKIHS mortuary, a focal point in eastern Nepal Study variables: Demographic characteristics of the victims, time, day and month of accidents, type of accidents, vehicle involved in accidents etc. Statistical analysis: Proportion. Results: There were approximately 78% male and 22% female road traffic accident victims with head injury. Students were the highest (20.7%) among the victims. The highest number of accidents took place in the month of June (11.7%) and on Saturdays (24.6%). The pedestrians were the largest (45%) group of the victims. Among the motorized vehicles, two wheeler drivers were more (34%) victims in accidents. Out of 77 fatalities, 22% were found to have consumed alcohol. Conclusion: Due to bad and mismanaged roads and poor road traffic knowledge to the citizens, road traffic accidents are the most common cause of unnatural deaths in this region. Minimal use of helmet is the main cause of fatal head injury in two wheeler occupants. Keywords: Head injury; Road traffic accident; Epidemiological study; Trauma; Injuries DOI: 10.3126/hren.v8i2.4420 Health Renaissance, May-Aug 2010; Vol 8 (No.2):97-101